Traffic accidents in Slovenia – the influence of the lunar phases - Kajdič, Primož (Anali PAZU, 2022)
In this work I analyse the frequency of traffic accidents in the Republic of Slovenia during the period from January 1, 1995 to June 30, 2010 and I compare this frequency with the phases of the Moon. During this period (5845 days) 635271 traffic accidents occurred. In 3984 cases the outcome of the accidents was death of at least one of the participants. This means that in Slovenia the average daily number of traffic accidents was 108.7 and the average number of accidents resulting in death was 0.68 per day. The comparison with the phases of the Moon showed that the average number of accidents during the full moon is the same as the average number of accidents when the Moon is in any other phase. This means that there is no proof that the Moon would have any kind of influence on the happening in the traffic.